2013
DOI: 10.1038/nn.3454
|View full text |Cite
|
Sign up to set email alerts
|

Sensory cortex limits cortical maps and drives top-down plasticity in thalamocortical circuits

Abstract: SummaryPrimary somatosensory cortex (S1) contains a complete body map that mirrors subcortical maps developed by peripheral sensory input projecting to sensory hindbrain, thalamus, then S1. Peripheral changes during development alter these maps through ‘bottom-up’ plasticity. Unknown is how S1 size influences map organization and if an altered S1 map feedbacks to affect subcortical maps. We show in mice that S1 is significantly reduced by cortex-specific deletion of Pax6, resulting in a reduced body map and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 50 publications
3
51
0
Order By: Relevance
“…We examined Emx1Cre YL ;Pax6 cKO brains for evidence of cellular barrel walls and found that GAP43 expression does indeed display a barrellike expression pattern in an appropriate region of the Pax6 cKO cortex (Fig. 7 G and I), reduced in size as has been previously reported (21,22). Because both barrel walls and barrel cores form in the absence of Pax6, it is unlikely that Pax6 is a major target of Lhx2 with respect to the regulation of barrel formation.…”
Section: -H)mentioning
confidence: 52%
See 1 more Smart Citation
“…We examined Emx1Cre YL ;Pax6 cKO brains for evidence of cellular barrel walls and found that GAP43 expression does indeed display a barrellike expression pattern in an appropriate region of the Pax6 cKO cortex (Fig. 7 G and I), reduced in size as has been previously reported (21,22). Because both barrel walls and barrel cores form in the absence of Pax6, it is unlikely that Pax6 is a major target of Lhx2 with respect to the regulation of barrel formation.…”
Section: -H)mentioning
confidence: 52%
“…Upon cortex-specific loss of Pax6, a reduction in superficial layer neurons, similar to the defect in the Lhx2 cKO brain (17), is seen because of the premature exit of ventricular zone progenitors from the cell cycle (18). However, whisker-specific cytochrome oxidase-expressing barrel cores (21,22) as well as cellular barrel walls (this study) do form in the absence of Pax6. Therefore, a decrease in cortical neuronal number may not by itself explain the loss of barrel formation in the Lhx2 cKO.…”
Section: Emx1crementioning
confidence: 54%
“…This disordered pattern is propagated through afferent pathways to SI, where a jumbled representation of the hand replaces the normal somatotopic arrangement [101]. However, if the median nerve is severed very early in development, a considerable degree of somatotopy is retained in SI [102], suggesting that early in development, an existing cortical body map can direct the reorganization of thalamocortical projections following a disruption in the orderly patterning at the periphery [103]. …”
Section: Figurementioning
confidence: 99%
“…This analysis shows that deletion of Lhx2 in postmitotic neurons broadly alters neuronal properties that affect area patterning across layers in the CP. (14,17,18), CoupTF1 (chicken ovalbumin upstream promoter transcription factor) (1,19), and Sp8 (specificity protein 8) immunolabelings (20,21) on E12 sagittal sections. The expression of TFs remained unchanged in the VZ in cKO sections (Fig.…”
Section: Significancementioning
confidence: 99%